Bridging social and environmental risks: the potential for an emerging environmental justice framework in South Africa. Issue 1 (2nd January 2018) - Leonard, Llewellyn
ABSTRACT: Whereas anti-apartheid social movements engaged collectively against a repressive regime, especially in actions against social injustices, post-apartheid civil society has witnessed fragmentation when it comes to engaging jointly against neoliberal risks such as poor/no service delivery, privatisation, and environmental pollution. Civil society has not linked struggles into a coherent ideology to comprehensively challenge neoliberalism and associated risks. Research has not explored the underlying elements that contribute to reinforcing fragmentation. This article reviews the literature on key social and environmental struggles in order to draw out common elements and differences that reinforce fragmentation. The paper highlights the need for social and environmental activists to engage collectively both within their respective arenas, as well as across the social and environmental divide, if an environmental justice framework is to emerge. Social movements advocating social justice could serve as a platform to incorporate environmental discourses into their struggle to assist in formulating an environmental justice framework.